KONTRIBUSI MOTIVASI, FASILITAS, DAN LINGKUNGAN BELAJARTERHADAP KEMANDIRIAN DALAM PEMBELAJARANMATEMATIKA SISWA KELAS X DI SMK MUHAMMADIYAH 2KLATEN UTARA SEMESTER GENAP TAHUN 2015/2016 - Febriantika, Nilam; , Prof. Dr. Sutama M,Pd (2016)
The research this purpose is: (1) the effect of motivation learning for students independence, (2) the effect of facility learning for students independence, (3) the effect of environment learning for students independence, and then the effect of motivation, facility and environment learning for students independence. This research is a quantitative research use correlational design. The population on this research it's their students class X at SMK Muhammadiyah 2 Klaten Utara, periode 2015/2016. The research sample consist of 162 students. The writer use proporsional random sampling technic. Collecting data use inquiry method and documentation method. Analysis data technic use double regression with significant standart 5%. Be based on hypotheses trial, resulting conclusion that: (1) There are effect of motivation learning for students independence, (2) There are not effect of facility learning for students independence, (3) the effect of environment learning for students independence. (4) There are effect of environment learning for students independence, and then the effect of motivation, facility and environment learning for students independence